Transformasi Agile Bisnis Media Menuju Keunggulan Kompetitif (Studi Kasus: Progam Lintas INews Siang MNCTV) - Pakan, Christian Kevin L; Gusfa, Henni (Universitas Merdeka Malang, 2024)
This research analyzes the agile transformation of the media business in creating competitive advantages in MNC TV's Lintas Inews Siang program. This research uses a qualitative approach with a case study method, data collection techniques through interviews, observation and documentation. The selection of informants used purposive sampling techniques and data analysis by means of data reduction, data presentation and drawing conclusions. The validity of the data was tested using triangulation techniques. The research results show that this program provides information that is relevant to community needs. Utilization of various platforms, conventional television and digital media, to expand audience reach. This program shows agility in managing news dynamics, as well as the ability to adapt. In addition, applying the principles of efficiency and effectiveness in operations optimizes resources, including regular evaluations to improve content quality and maintain a competitive advantage in the market.